Usage and motives of urban river corridor: a case study at Hutuo River in Shijiazhuang, Hebei Province, China - Lin, Shi; Maruthaveeran, Sreetheran; Mohd Yusof, Mohd Johari (Elsevier, 2024)
The study provides important managerial implications suggesting socio-demographics can influence the experience in the usage and motives of visitation. It is essential to consider the different interests and motives of users from different socio-demographic backgrounds in order to attract visitors to the place. In responding to the different socio-demographic groups, it is also essential for the management to create a variety of activities at the river corridor. By creating recreational opportunities will enhance not only more visitors but from all levels of groups. This study also aligns with the ideals of people-oriented design, catering to public aesthetics and lifestyle requirements while fostering sustainability in the development of river corridor landscapes.